2013
DOI: 10.1017/thg.2013.29
|View full text |Cite
|
Sign up to set email alerts
|

CNV Analysis in Monozygotic Twin Pairs Discordant for Urorectal Malformations

Abstract: Early post-twinning mutational events can account for discordant phenotypes in monozygotic (MZ) twin pairs. Such mutational events may comprise genomic alterations of different sizes, ranging from single nucleotides to large copy-number variations (CNVs). Anorectal malformations (ARM) and the bladder exstrophy-epispadias complex (BEEC) represent the most severe end of the urorectal malformation spectrum. Recently, CNV studies in patients with sporadic ARM and the BEEC have identified de novo events that occur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…The reported conclusions were contradictory. Baudisch et al . showed that no potentially causative CNV remained after applying the filter criteria for detection CNVs leading to urorectal malformations.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The reported conclusions were contradictory. Baudisch et al . showed that no potentially causative CNV remained after applying the filter criteria for detection CNVs leading to urorectal malformations.…”
Section: Discussionmentioning
confidence: 93%
“…Postnatal studies that reported the different distribution of CNVs in discordant MZ twins are involved in many types of diseases, including CHD, urorectal malformations, schizophrenia, Parkinson disease, congenital diaphragmatic hernia, esophageal atresia, attention problems and so on. The reported conclusions were contradictory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies with monozygotic twins can be decisive in the elucidation of the molecular mechanisms involved in the development of congenital diseases in humans, especially because, in contrast to other individuals, monozygotic twins share similar prenatal environments as well as a common genetic background [13]. In this study, we identified 40,123 SNVs in the proband.…”
Section: Discussionmentioning
confidence: 90%